The Composer’s Program Note for Newly Written Classical Music: Content and Intentions - Blom, Diana M.; Bennett, Dawn; Stevenson, Ian (Frontiers in Psychology, 2016)
In concerts of western classical music the provision of a program note is a widespread practice dating back to the 18th century and still commonly in use. Program notes tend to inform listeners and performers about historical context, composer biographical details and compositional thinking. However, the scant program note research conducted to date reveals that program notes may not foster understanding or enhance listener enjoyment as previously assumed. In the case of canonic works, performers and listeners may already be familiar with much of the program note information. This is not so in the case of newly composed works, which formed the basis of the exploratory study reported here. This article reports the views of 17 living contemporary composers on their writing of program notes for their own works. In particular the study sought to understand the intended recipient, intended role and the content of composer-written program notes. Participating cComposers identified three main roles for their program notes: to shape a performer’s interpretation of the work; to guide, engage or direct the listener and/or performer; and as collaborative mode of communication between the composer, performer and listener. For some composers this collaboration was intended to result in “performative listening” in which listeners were actively engaged in bringing each composition to life. This was also described as a form of empathy that results in the co-construction of the musical experience. Overall, composers avoided giving too much personal information and they provided performers with more structural information. However, composers did not agree on whether the same information should be provided to both performers and listeners. Composers’ responses problematize the view of a program note as a simple statement from writer to recipient, indicating instead a more complex set of relations at play between composer, performer, listener and the work itself. These relations are illustrated in a proposed model. There are implications for program note writers and readers, and for educators. Future research might seek to enhance understanding of program notes, including whether the written program note is the most effective format for communications about music.